Method for evaluating hydrogen embrittlement sensitivity of high-strength mooring chain

By pre-straining and electrochemical testing of high-strength mooring chains, combined with slow strain rate tensile testing and hydrogen content determination, the problem of the inability to quantitatively analyze the effect of pre-strain in traditional methods has been solved, achieving high-precision evaluation of hydrogen embrittlement sensitivity and improving the safety and quality of mooring chains.

CN121141499BActive Publication Date: 2026-03-17JIANGSU ASIAN STAR ANCHOR CHAIN +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511685243.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-18
Publication Date
2026-03-17
Estimated Expiration
2045-11-18

AI Technical Summary

Technical Problem

Traditional methods are insufficient to accurately evaluate the hydrogen embrittlement sensitivity of high-strength mooring chains, especially under pre-strain conditions, as they cannot quantitatively analyze the impact and cannot simulate actual service conditions.

Method used

By pre-straining high-strength mooring chain specimens, combined with electrochemical testing, slow strain rate tensile testing, and hydrogen content determination, the influence of pre-strain rate on hydrogen embrittlement sensitivity was quantitatively analyzed to simulate the actual service environment.

Benefits of technology

It improves the accuracy of hydrogen embrittlement sensitivity evaluation, enables more accurate assessment of the impact of pre-strain on chain links, ensures product quality and safety, and provides scientific experimental basis for optimizing material selection and processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121141499B_ABST
    Figure CN121141499B_ABST
Patent Text Reader

Abstract

This invention discloses a method for evaluating the hydrogen embrittlement susceptibility of high-strength mooring chains, belonging to the field of material performance evaluation technology. The method first involves taking samples from the non-welded area of ​​the chain links and subjecting them to pre-stretching treatment at a predetermined strain rate to simulate the stress history of the mooring chain's factory tensile test. Subsequently, electrochemical hydrogen charging and slow strain rate tensile tests are conducted on the samples before and after pre-straining in a simulated seawater environment. Finally, the influence of the pre-strain rate on hydrogen embrittlement susceptibility is quantitatively evaluated by analyzing the mechanical properties, fracture morphology, and hydrogen content changes of the samples. This invention, by introducing a pre-straining step, makes the evaluation conditions closer to the actual service state of the mooring chain, overcoming the limitation of traditional methods that cannot consider the influence of pre-strain, and providing a more accurate and scientific basis for the safety and reliability assessment of high-strength mooring chains.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of material performance evaluation technology, and in particular to a method for evaluating the hydrogen embrittlement sensitivity of high-strength mooring chains. Background Technology

[0002] Mooring chains are crucial equipment for mooring and positioning of offshore floating hulls, becoming an indispensable component of mooring systems due to their excellent load-bearing capacity, fatigue resistance, and wear resistance. As offshore floating hulls expand into deeper waters, the need for lightweight mooring chains becomes increasingly urgent, requiring higher chain link strength. Hydrogen embrittlement has become a key factor limiting chain link performance. Furthermore, during service, the cathodic protection system of the floating hull partially covers the mooring chain, leading to localized increases in hydrogen concentration within the chain links, further exacerbating the risk of hydrogen embrittlement. Traditional evaluation methods are insufficient to accurately reflect hydrogen embrittlement sensitivity; therefore, an efficient and precise evaluation method is urgently needed to ensure the safety and reliability of deep-sea mooring systems.

[0003] Mooring chains are made of low-alloy high-strength steel through flash welding, followed by quenching and tempering to achieve good comprehensive mechanical properties. Currently, the highest grade R6 mooring chains have a strength exceeding 1100 MPa. Therefore, their hydrogen embrittlement susceptibility should be evaluated when serving in corrosive marine environments. Before leaving the factory, in addition to visual and dimensional inspections, mooring chains undergo tensile load tests to check weld reliability. The tensile load is typically 70-80% of the breaking load, with some areas approaching or even exceeding the material's yield strength. Traditional methods usually involve directly cutting tensile specimens from the research object and analyzing them using electrochemical hydrogen charging combined with slow tensile testing. However, this approach cannot study the effect of pre-strain on the product's hydrogen embrittlement susceptibility, thus having limitations. Furthermore, using actual chain links for pre-strain tensile testing reveals differences in strain rates at different locations, making quantitative analysis impossible.

[0004] Therefore, this invention proposes a novel evaluation method that simulates chain link tensile tests by pre-straining the specimen. By combining tensile tests and hydrogen content testing, the influence of pre-strain rate on the hydrogen embrittlement sensitivity of the specimen can be quantitatively analyzed, thereby improving the evaluation accuracy. Summary of the Invention

[0005] The purpose of this invention is to solve the above-mentioned technical problems and provide a method for evaluating the hydrogen embrittlement sensitivity of high-strength chain links under pre-strain conditions. This method can quantitatively analyze the influence of pre-strain rate on the hydrogen embrittlement sensitivity of the sample, improve the evaluation accuracy, and more closely reflect the actual service conditions.

[0006] To achieve the above technical objectives and meet the above technical requirements, the technical solution adopted by this invention is: a method for evaluating the hydrogen embrittlement sensitivity of a high-strength mooring chain, comprising the following steps:

[0007] Step 1, Specimen Preparation: In-situ hydrogen-filled tensile specimens and pre-strained tensile specimens are cut from the non-welded portion of the high-strength mooring chain link to be evaluated.

[0008] Step 2, Pre-strain treatment: The pre-strained tensile specimens from Step 1 are subjected to pre-strain treatment using a universal tensile testing machine; the pre-strain rate of the pre-strain treatment is set according to the actual strain level of the mooring chain's tensile test at the factory, preferably 0.5%-3%; the tensile rate is controlled within the range of 1.5mm / min-2.5mm / min.

[0009] It should be noted that the pre-strain rate range of 0.5%-3% in this invention is based on a thorough consideration of the mechanical behavior of high-strength mooring chain steel and actual manufacturing processes. Firstly, uniaxial tensile tests on the high-strength mooring chain steel confirmed that its uniform plastic deformation capacity is sufficient to cover a strain level up to 3% without necking or fracture. Secondly, this range fully covers the actual strain level generated by the mooring chain product during factory tensile load tests (typically 70%~80% of the breaking load), ensuring that the laboratory pre-strain treatment can effectively simulate the product's true stress history. Therefore, the setting of this pre-strain rate range is scientific and consistent with engineering practice.

[0010] Step 3: Sample taking: After pre-straining, use an electrical discharge wire cutter to precisely cut standard test samples from the uniform deformation area of ​​the pre-strained sample for subsequent hydrogen embrittlement sensitivity testing.

[0011] Step 4: Electrochemical testing: For the original hydrogen-charged tensile specimens without pre-strain treatment and the test specimens after pre-strain treatment, potentiodynamic cathodic polarization curve tests were performed at room temperature in a 3.5wt% NaCl aqueous solution simulating a seawater environment to determine the range of cathodic protection potentials to be used for subsequent electrochemical hydrogen charging.

[0012] Step 5, Electrochemical Pre-charging with Hydrogen: The original sample and the pre-strained sample were placed in a 3.5 wt% NaCl aqueous solution and subjected to constant potential pre-charging with hydrogen at different cathodic protection potentials determined in Step 4; the pre-charging time was 2-3 hours, and the charging current density was 9 mA / cm². 2 ~11mA / cm 2 This is to ensure that hydrogen atoms fully penetrate into the material;

[0013] Step 6: Slow strain rate tensile test: The pre-hydrogen-charged specimens are subjected to a slow strain rate tensile test. The tensile rate is controlled within the range of 0.004 mm / min to 0.006 mm / min until the specimen breaks, so as to obtain the tensile strain-stress curves under different cathodic protection potentials and calculate the reduction of area of ​​the specimen.

[0014] Step 7: Fracture morphology analysis: The fracture morphology of the fractured sample from Step 6 is observed and analyzed using a scanning electron microscope (SEM) to determine the degree of hydrogen embrittlement.

[0015] Step 8: Hydrogen content determination: The hydrogen concentration of the original sample and the pre-strained sample at different cathodic protection potentials was measured using a thermal desorption spectrometer (TDS).

[0016] Step 9: Evaluation and Comparative Analysis of Hydrogen Embrittlement Sensitivity: Combining the mechanical property data obtained in Step 6, the fracture morphology analysis results in Step 7, and the hydrogen content data in Step 8, the changes in hydrogen embrittlement sensitivity of the samples before and after pre-strain treatment are compared and analyzed to quantitatively evaluate the influence of pre-strain on the hydrogen embrittlement sensitivity of high-strength mooring chain steel.

[0017] Compared with the traditional structure, the beneficial effects of the present invention are as follows:

[0018] 1. This invention, through controlled pre-strain treatment of the sample, combined with multi-stage experiments such as potentiodynamic cathodic polarization curve testing, pre-hydrogen charging treatment, slow strain rate tensile test, fracture morphology analysis and hydrogen concentration measurement, can quantitatively analyze the influence of pre-strain rate on the hydrogen embrittlement sensitivity of high-strength mooring chains. It overcomes the shortcomings of traditional methods that cannot quantitatively study the influence of pre-strain and significantly improves the accuracy of hydrogen embrittlement sensitivity evaluation.

[0019] 2. The experimental environment adopted a 3.5wt% NaCl aqueous solution at room temperature to simulate the marine corrosion environment of the mooring chain in actual service. At the same time, the pre-strain treatment simulated the tensile load test before the mooring chain left the factory and the pre-strain state that may occur during actual service, making the evaluation process more consistent with the actual working conditions of the mooring chain.

[0020] 3. This invention can not only obtain macroscopic mechanical property data such as strain-stress curves and reduction of area of ​​the specimen, but also obtain microscopic fracture mechanism information through fracture morphology analysis. Combined with hydrogen concentration measurement data, it can comprehensively evaluate from macroscopic performance to microscopic mechanism, and the conclusions are scientific and reliable.

[0021] 4. This method can provide important experimental basis and data support for the selection of high-strength mooring chain materials, optimization of heat treatment processes, and formulation of pre-shipment tensile process specifications. While ensuring the reliability of the weld, it can reduce the risk of hydrogen embrittlement caused by pre-strain and improve the quality and safety of mooring chain products. Attached Figure Description

[0022] Figure 1 This is a schematic diagram of the structure of the in-situ hydrogen-filled tensile specimen of the present invention;

[0023] Figure 2 This is a schematic diagram of the pre-strained tensile specimen of the present invention;

[0024] Figure 3 This is a schematic diagram showing the sampling location for taking test specimens from the pre-strained specimen.

[0025] Figure 4 The original sample is shown as the cathodic polarization curve of the potentiodynamics in 3.5 wt% NaCl solution.

[0026] Figure 5 The cathodic polarization curves of the sample after 1% pre-strain treatment in 3.5 wt% NaCl solution are shown.

[0027] Figure 6 The stress-strain curves of the original specimens obtained from slow tensile tests under different cathodic protection potentials are shown.

[0028] Figure 7 The stress-strain curves of the specimens after 1% pre-strain treatment were obtained by slow tensile tests at different cathodic protection potentials.

[0029] Figure 8 The cathodic polarization curves of the sample after 3% pre-strain treatment in 3.5 wt% NaCl solution are shown.

[0030] Figure 9 The stress-strain curves of the specimens after 3% pre-strain treatment were obtained by slow tensile tests at different cathodic protection potentials.

[0031] in, Figure 4 and Figure 5 , Figure 8 The numbers "1", "2", and "3" in the figure represent three repeated experiments under the same conditions. Their curves highly overlap, indicating the good repeatability and accuracy of the method and experimental results of this invention. Detailed Implementation

[0032] The present invention will be further described below.

[0033] Example: Using an R6 grade high-strength mooring chain (strength approximately 1100 MPa) as the evaluation object, hydrogen embrittlement sensitivity was evaluated according to the evaluation method steps of this invention. For specific illustration, a 1% pre-strain is used as an example for detailed description below; however, it should be understood that the method of this invention is also applicable to other pre-strain rates such as 0.5%, 2%, and 3%. The specific operation is as follows:

[0034] (1) Sample preparation: A sample is taken from the non-welded part of the high-strength mooring chain link, such as... Figure 1The I-shaped in-situ hydrogen-charged tensile specimen shown has a symmetrical structure. The specimen has clamping sections at both ends and four through holes for connection to the testing machine. The middle section of the specimen forms its core parallel gauge length segment, which is the core area for hydrogen-charged and slow strain rate tensile testing. A rounded transition is provided between the parallel gauge length segment and the clamping sections to effectively avoid stress concentration during tensile testing. In a preferred embodiment, the key dimensions of the specimen are as follows: total specimen length L1 is 48 mm, total width H1 is 18 mm, thickness is 1.2 mm, effective length L2 of the parallel gauge length segment is 20 mm, and width H2 is 3 mm.

[0035] (2) Pre-strain treatment: The specimens are pre-strained using a universal tensile testing machine. The tensile rate is set to 1.5~2.5 mm / min, preferably 2.0 mm / min. The pre-strain rate is set according to the actual strain level of the mooring chain's tensile test at the factory, and is preferably 0.5%-3% based on the material's plastic deformation capacity. In one specific embodiment, 1% pre-strain is applied before unloading. The shape and dimensions of the pre-strained tensile specimen are as follows: Figure 2 As shown, its total length L3 is 100mm, total width H3 is 35mm, and thickness is 4.7mm. The effective length L4 of the middle parallel gauge length section is 28mm, and the width H4 is 19mm. This is the core area for pre-strain, hydrogen-filled, and slow strain rate tensile tests.

[0036] (3) Sample taking for testing: according to Figure 3 The scheme shown uses a wire electrical discharge machine to precisely cut out samples from the uniform deformation region of the pre-strained tensile specimen. Figure 1 The standard test specimens shown are I-shaped specimens and 7*7 square specimens, the square specimens being used for material microstructure analysis.

[0037] (4) Electrochemical testing: For the untreated original sample and the 1% pre-strained sample, potentiodynamic cathodic polarization curves were tested at room temperature in a 3.5wt% NaCl aqueous solution simulating a seawater environment. The results are as follows: Figure 4 , Figure 5 As shown, the range of hydrogen-charged cathodic protection potential for the experiment was determined to be -600 to -1500 mV.

[0038] (5) Electrochemical pre-charging with hydrogen: The original sample without pre-strain treatment and the 1% pre-strain sample were placed in a 3.5wt% NaCl aqueous solution and pre-charged with hydrogen at different cathodic protection potentials; the pre-charging time was 2-3h, preferably 2.5h, and the hydrogen charging current density was 9-11mA / cm 2 10mA / cm is preferred 2 This is to ensure that hydrogen atoms fully penetrate into the material.

[0039] (6) Slow strain rate tensile test: At a tensile rate of 0.004~0.006 mm / min, preferably 0.005 mm / min, a slow strain rate tensile test was performed on the specimens before and after hydrogen charging until the specimens fractured. The tensile strain-stress curves were recorded (the results are shown in the figure). Figure 6 , Figure 7 (as shown), and calculate the section reduction rate.

[0040] (7) Fracture morphology analysis: The fracture morphology of the samples was observed and analyzed using a scanning electron microscope (SEM). The degree of hydrogen embrittlement was quantitatively or semi-quantitatively determined by calculating the relative proportion of the area occupied by hydrogen embrittlement features such as intergranular fracture and quasi-cleavage fracture on the fracture surface. The results showed that the proportion of hydrogen embrittlement features in the fracture surface increased with the negative shift of the cathode potential.

[0041] (8) Hydrogen content determination: The hydrogen concentration of the original sample and the pre-strained sample was measured using a thermal desorption spectrometer (TDS) at different cathodic protection potentials. The test results showed that the hydrogen content of the pre-strained sample was higher than that of the original sample under the same hydrogen charging conditions.

[0042] (9) Evaluation and Comparative Analysis of Hydrogen Embrittlement Sensitivity: Combining the mechanical property data obtained in step six, the fracture morphology analysis results in step seven, and the hydrogen content data in step eight, the changes in hydrogen embrittlement sensitivity of the samples before and after pre-strain treatment were compared and analyzed to quantitatively evaluate the effect of pre-strain on the hydrogen embrittlement sensitivity of high-strength mooring chain steel. The comparison revealed that 1% pre-strain significantly improved the hydrogen embrittlement sensitivity of this steel at a specific cathode potential, providing a scientific basis for the reliability assessment of high-strength chain links in practical applications and a reference for the formulation of the stretching process before the chain leaves the factory.

[0043] To further verify the universality of the method of the present invention within the stated pre-strain rate range, the same evaluation procedure was also performed on specimens with a 3% pre-strain rate. The corresponding potentiodynamic cathodic polarization curves and stress-strain curves of the slow strain rate tensile tests are shown below. Figure 8 and Figure 9 As shown in the figure. Experimental results show that even at pre-strain rates as high as 3%, the specimens did not experience necking or premature fracture before hydrogen charging and during slow stretching, and their hydrogen embrittlement sensitivity variation pattern was consistent with that of the 1% pre-strain specimens. Furthermore, the same method was used to evaluate specimens with pre-strain rates of 0.5% and 2%. The results showed that within the entire pre-strain rate range of 0.5%-3%, the specimens did not experience premature fracture, and the hydrogen embrittlement sensitivity exhibited a regular change with increasing pre-strain rate, further verifying the effectiveness and feasibility of the method of the present invention across the entire parameter range.

[0044] The above embodiments of the present invention are merely examples to clearly illustrate the present invention, and are not intended to limit the scope of protection of the present invention. All equivalent technical solutions also fall within the scope of the present invention, and the patent protection scope of the present invention should be defined by the claims.

Claims

1. A method for evaluating the susceptibility to hydrogen embrittlement of a high-strength mooring chain, characterized by: The method comprises the following steps: Step one, sample preparation: in-situ hydrogen-charged tensile samples and pre-strain tensile samples are cut from non-welded parts of high-strength mooring chain links to be evaluated; Step two, pre-strain treatment: the pre-strain tensile samples of step one are subjected to pre-strain treatment to simulate the strain level of the mooring chain factory tensile test; the pre-strain rate of the pre-strain treatment is 0.5%-3%; Step three, test sample sampling: after the pre-strain treatment, a standard test sample for subsequent hydrogen embrittlement sensitivity test is accurately cut from the uniform deformation area of the pre-strain sample using an electric spark wire cutting machine; Step four, electrochemical test: the original hydrogen-charged tensile sample without pre-strain treatment and the test sample after pre-strain treatment are subjected to potentiodynamic cathodic polarization curve test in a 3.5wt% NaCl aqueous solution simulating seawater environment at room temperature, so as to determine the cathodic protection potential range; Step five, electrochemical pre-charging hydrogen: the original sample and the pre-strain treated sample are placed in 3.5wt% NaCl aqueous solution, and constant potential pre-charging hydrogen treatment is carried out at different cathode protection potentials determined in step four; the electrochemical pre-charging hydrogen is carried out in 3.5wt% NaCl aqueous solution, the pre-charging hydrogen time is 2-3h, and the hydrogen charging current density is 9mA / cm 2 11mA / cm 2 to ensure that hydrogen atoms fully penetrate into the material. Step six, slow strain rate tensile test: the pre-hydrogen-charged sample is subjected to slow strain rate tensile test, the tensile rate is controlled in the range of 0.004mm / min~0.006mm / min, until the sample is broken, so as to obtain the tensile strain-stress curve under different cathodic protection potentials, and calculate the sample fracture section shrinkage rate; Step seven, fracture morphology analysis: the fracture morphology of the fractured sample in step six is analyzed by scanning electron microscope; Step eight, hydrogen content determination: the hydrogen concentration of the original sample and the sample after pre-strain treatment under different cathodic protection potentials is measured by thermal desorption spectrometer TDS; Step nine, hydrogen embrittlement sensitivity evaluation and comparative analysis: the hydrogen embrittlement sensitivity changes of the samples before and after pre-strain treatment are compared and analyzed by comprehensively analyzing the mechanical property data obtained in step six, the fracture morphology analysis results in step seven and the hydrogen content data in step eight, so as to quantitatively evaluate the influence of pre-strain on the hydrogen embrittlement sensitivity of high-strength mooring chain steel.

2. The method of evaluating the susceptibility of hydrogen embrittlement of a high-strength mooring chain according to claim 1, characterized by: In step one, the middle part of the in-situ hydrogen-charged tensile sample and the pre-strain tensile sample has a parallel gauge section, and both ends are provided with clamping parts, and the clamping parts and the parallel gauge section are smoothly connected through a circular arc transition.